Hubungan Aktivitas Fisik Dengan Kualitas Hidup Pada Pasien Kanker Serviks Yang Menjalani Kemoterapi Di Rsud Dr Moewardi Surakarta - Hananingrum, Ratri Wijayanti; , Okti Sri Purwanti. S.Kep., M.Kep., Ns. Sp.Kep.M.B (2017)
Cervical cancer patients often dealing psychosocial problems and physical problems during and after cancer treatment, such as decreased physical activity and physical function. The long-term consequences of these problems can affect the health of patients related to quality of life. The lower physical activity of a person will affect quality of life in general. The purpose of this study to determine the tionship between physical activity with quality of life in cervical cancer patients who underwent chemotherapy in RSUD Dr. Moewardi Surakarta The research type is quantitative, with descriptive correlative research design, and cross sectional approach. The population in this study is all cervical cancer patients who underwent chemotherapy in RSUD Dr. Moewardi Surakarta, the population of January 2017 was 107 people, the sample was 52 respondents and the sampling technique is accidental sampling. The equipment measurement with Baecke and EORTC QLQ-C30 questionnaires. Analysis of data with univariate and bivariate with spearman rank. The research results of physical activity of cervical cancer patients who underwent chemotherapy in RSUD Dr. Moewardi Surakarta mostly doing medium physical activity. The quality of life in cervical cancer patients undergoing chemotherapy is high. There is a relationship between physical activity and quality of life in cervical cancer patients who underwent chemotherapy with p value 0.003 <0.05 with moderate relationship strength. The conclusion is there is a relationship between physical activity and quality of life in cervical cancer patients who underwent chemotherapy. Motivation and palliative care needed to cervical cancer patients who undergo chemotherapy to keep have spirit of life and keep doing physical activity so they have a good quality of life.